PKP-027 Significant interactions in treatment of dravet syndrome. (14th February 2016) - Idoate, AI; Aldaz, A; Parra, A; Sanchez-Carpintero, R
Abstract : Background: Standard combined treatment of Dravet syndrome, which includes clobazam (CLO), stiripentol (STI) and valproate (VPA), frequently presents adverse behavioural effects. Purpose: To determine the association between the presence and degree of behavioural alterations and possible kinetic-dynamic interactions of treatment of Dravet syndrome. Material and methods: A single centre, retrospective, observational study was carried out in children treated at our centre for Dravet syndrome from January 2011 to September 2015. Children selected had received simultaneous treatment with VPA, STI and CLO. Metabolic indicators and concentration/dose normalised by weight were estimated based on plasma concentrations of CLO and its active metabolite, norclobazam (NorCLO), before and at least 4 days after administration of STI. STI possible influence on VPA kinetics and dynamics was also analysed. Results: 16 patients were analysed, of whom 7 (4 females), with a mean age of 9.5 years, had received simultaneous treatment with all 3 drugs. The mean daily doses administered were 12.1 mg (CLO), 551.2 mg (STI) and 771.9 mg (VPA). The mean concentration/dose normalised by weight for CLO and NorCLO before STI was added were 482.1 and 3791.6 ng/mL, respectively. The addition of STI, with a mean concentration at steady state of 12.1 ng/mL, was associated with an increase in the concentration of CLO and NorCLO by 68.1% and 69.3%, respectively. The mean values were 810.3 and 12351.9 ng/mL, respectively. Children with NorCLO concentrations of >5000 ng/mL experienced major changes in their behaviour (irritability, insomnia, aggressiveness). VPA concentrations increased by 1.6% on average, with a 5.3% decrease in clearance after addition of STI, athough these results were not statistically significant. Conclusion: Adding STI to the standard regimen of VPA and CLO leads to significant increases in plasma concentrations of CLO and NorCLO due to STI's strong inhibitory effect on CYP2C19 and, to a lesser degree, on CYP3A4. Potentially toxic values of CLO and its metabolite NorCLO are produced which are associated with a marked deterioration in patient behaviour. This does not occur with VPA. Concentrations of CLO and NorCLO should be closely monitored in combined therapy with STI and the dose should be adjusted to clinical needs. No conflict of interest.